The Effect Of Mutation and Rotation On Employee Performance at The BPJS Employment Office Palu City Branch - Sartika, Andi Triayu; Nurman, Nurman; Natsir , Uhud Darmawan; Burhanuddin , Burhanuddin; Ali , Ahmad (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Employee performance is one aspect that must be considered in a company. This study aims to test whether Mutation and Rotation Variables affect Employee Performance at the BPJS Employment Office Palu City Branch. The population in the study was 50 employees. While the sample in the study was employees who received mutations and rotations as many as 36 employees. The data collection technique used is a questionnaire. The collected data is analyzed and then fed into multiple linear regression equations. The findings in this study show that some Mutation Variables have a negative insignificant effect on Employee Performance at the BPJS Employment Office Palu City Branch. Conversely, the Rotation Variable shows partial results that Rotation has a positive and significant effect on Employee Performance at the BPJS Employment Office Palu City Branch. While the simultaneous results show that the Mutation Variable and the Rotation Variable together have a positive and significant effect on Employee Performance at the BPJS Employment Office Palu City Branch.